Ice hockey skate, stick design and performance measures - Turcotte, R. A.; Renaud, P.; Pearsall, D. J.. (The engineering approach to winter sports, 2016)
Ice hockey has a long history dating back to the 1880s in Canada and Europe. The game has evolved, especially in the last two decades into a fast-paced power game. !ce hockey has become increasingly sophlsticated in terms of technological innovations, equipment design and improvements in training, coaching and game strategies. This has led to a game where players accenltuate speed and power to a greater extent than previous generations of hockey players. However, in nearly two decades of research in this area it is understood that although speed and power have been optimized, skate development has also had implications for the improvement of a range of skating skills, some of which require finesse and precision for optimal execution. The unique environrnental conditions (e.g. low surface friction of ice hockey demand a very distinctive skiII set. The skating skiIIs in particular can be subdivided into skills that require power (forward and backward skating) and skills that require precision and or finesse during execution, such as changes in direction. The earliest records of the first known skate models are quite primitive in their design; but the goal behind them was the same: to allow a person to rnove and travel around faster on ice. Although today most ice hockey skates are used for leisure and sport, the earlier models of ice skates were fabricated in order to allow people to transport themselves across frozen waterways in cold climate cities. The intent of this section of the chapter is to examine the importance of skate design in relation to comfort, fit and performance for skating in ice hockey.